Measuring Economic Welfare : What and How? - Quiros-Romero, Gabriel (Policy Papers; Policy Paper, 2020)
Calls for a more people-focused approach to statistics on economic performance, and concerns about inequality, environmental impacts, and effects of digitalization have put welfare at the top of the measurement agenda. This paper argues that economic welfare is a narrower concept than well-being. The new focus implies a need to prioritize filling data gaps involving the economic welfare indicators of the System of National Accounts 2008 (SNA) and improving their quality, including the quality of the consumption price indexes. Development of distributional indicators of income, consumption, and wealth should also be a priority. Definitions and assumptions can have big effects on these indicators and should be documented. Concerns have also arisen over potentially overlooked welfare growth from the emergence of the digital economy. However, the concern that free online platforms are missing from nominal GDP is incorrect. Also, many of the welfare effects of digitalization require complementary indicators, either because they are conceptually outside the boundary of GDP or impossible to quantify without making uncertain assumptions.